A comprehensive study of the effect of meteorological conditions on fruit abscission and metamitron thinning efficacy in Malus domestica Borkh - Rosa, Nídia Diana Heleno (2022)
Doutoramento em Engenharia Agronómica / Instituto Superior de Agronomia. Universidade de Lisboa